Teachers' voices : storytelling and possbility - Elbaz-Luwisch, Freema (Issues in curriculum theory, policy, and research., 2005)
This book draws on ideas about the nature of teaching and teacher knowledge, teacher development and school reform, and narrative as methodology for understanding the lives and work of teachers. These ideas have been elaborated over the past 20 years or so by many researchers who see storytelling as the interactive process, which constitutes the site of the production of teachers' knowledge. Narrative research makes it possible to pay attention to the wider concerns that shape the work of teaching, looking at the whole lives of teachers and other educational practitioners, and exploring those lives as embedded in multiple contexts. Listening to teachers speak about whatever most concerns them in their work, it is not surprising that we hear a wide range of different voices not only from different teachers but within the speech of any one teacher. The purpose of this book is to reflect back to the field a multidimensional, multivoiced portrayal of teaching as it is, bringing our attention to both the complexity and the possibility inherent in the work of teachers. Approaching teaching in this way, as multivoiced, allows us to hear possibilities for change and development in the stories of teachers and classrooms.